Aurora 6 : Norrsken -94. - Arell, Berndt; Edwards, Folke; von Heland, Madeleine; Göteborgs Konstmuseum, Göteborg; The Nordic Arts Centre, Helsinki (Helsinki : Nordisk Konstcentrum, 1994)
Aalto, Johannes ; Ásgrímsdóttir, Hlíf ; Falk, Johannes ; Bollason, Gustav Geir ; Heier, Liv ; Nondal, Astrid ; Petersson, Hans ; Rosing, Ina ; Wilkman, Sofia ; Östlund, Svante
Published to accompany the exhibition: Göteborgs Konstmuseum, Göteborg, 1994-03-12 - 1994-04-24.
Published to accompany the exhibition: The Nordic Arts Centre, Helsinki, 1994-02-06 - 1994-07-31.
kunstcatalogus
Keywords: Scandinavië